THE ROLE OF INNOVATIVE INVESTMENTS IN THE SOCIO-ECONOMIC DEVELOPMENT OF THE REGION (International journal of artificial intelligence, 2026)
This study examines the role of innovative investments in regional socio-economic development using the case of Uzbekistan. The research is based on panel data covering 14 regions over the period 2010–2024 and applies econometric modeling to evaluate the impact of innovation-oriented investments on economic growth. The findings indicate that innovative investments have a significant positive effect on regional GDP growth, particularly when combined with human capital, demonstrating a strong synergistic effect. Furthermore, innovative investments contribute to industrial diversification, improvement of employment quality, and reduction of regional disparities. The results provide a scientific basis for enhancing regional innovation policies and improving the efficiency of investment allocation.